EVALUATION OF INCIDENCE AND RISK FACTORS OF MANUAL HANDLING ACTIVIETIES IN A CANNED FOOD WAREHOUSE - Tandean, Reza (E-Journal Widya Kesehatan dan Lingkungan, 2005)
The objectives of the study were 1) To investigate tge relationship between Manual Material Handling workers with muscloskeletal complaints; and 2) To identify possible demographic risk factors related to Manual Material Handling workers. This study was an observational descriptive study with the data collected by respondents answering through a pre- and the warehouse had one health clinic. A sample of 80 healthy men was randomly taken from the health clinic register. The data collected were the following : age, education, occupation history, marital status, length of employment, and health. Inclusion criteria were 1) manual material handling workers examined in good health; and 2) No absenteeism within the last 3 months. There were quite a number of workers with back pain complaints in this canned warehouse after doing Manual Material Handling taks. In this study the back pain increased with increasing age of non educated workers, and in their first year of employment.